Aegis or Achilles Heel: The Dilemma of Homology in Biopatents in the Wake of Novozymes - Yang, Qinghua (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
Biopatents frequently disclose sequences of polypeptides and nucleic acids in the written description. The claims often cover a homology range surrounding the disclosed sequence to get a broader protection. However, homology claims face a hurdle that they may lack support by the written description. The Supreme Court of China ruled that homology claims lack support, but a further limitation by species of origin satisfies this requirement. This study explains that homology per se should have formed the essence of such disputes. Homology dictates the skilled person$1 (Bs confidence on the functionality of unknown sequences, and is involved in multiple patentability requirements. Thus, the assessment of support is not an isolated matter. Disparity of different requirements creates an unclaimable gap, and constitutes a discrimination to biotechnology. An appropriate test for the support requirement is thus furnished to confer a scope of protection commensurating to the technical contribution.s
English
Keywords: polypeptide; homology; Achilles Heel; Biopatents; Novozymes; Chinese patent law; protein; Aegis Heel; support requirement; Dilemma of Homology